2019
DOI: 10.1002/advs.201802019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chloride Incorporation in Lead‐Free 2D Perovskite (BA)2SnI4: Morphology, Photoluminescence, Phase Transition, and Charge Transport

Abstract: The incorporation of chloride (Cl) into methylammonium lead iodide (MAPbI3) perovskites has attracted much attention because of the significantly improved performance of the MAPbI3‐based optoelectronic devices with a negligible small amount of Cl incorporation. It is expected that the Cl incorporation in 2D perovskites with layered nature would be much more efficient and thus can greatly alter the morphology, optical properties, phase transition, and charge transport; however, studies on those aspects in 2D pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 72 publications
5
41
0
Order By: Relevance
“…Of note, the chloride contents in the thin films are smaller compared with the respective chloride contents in precursor solutions, which implies most of the Cl ions leave the film during the fabrication process, likely during the SbI 3 vapor anneal step, consistent with other reports. [2,29] Nonetheless, each subsequent increase in SbCl 3 in the precursor solution ultimately contributed to an increase in final chloride ion content across the entire series. From here on, we will refer to the x values measured by EDXS rather than the theoretical value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the chloride contents in the thin films are smaller compared with the respective chloride contents in precursor solutions, which implies most of the Cl ions leave the film during the fabrication process, likely during the SbI 3 vapor anneal step, consistent with other reports. [2,29] Nonetheless, each subsequent increase in SbCl 3 in the precursor solution ultimately contributed to an increase in final chloride ion content across the entire series. From here on, we will refer to the x values measured by EDXS rather than the theoretical value.…”
Section: Resultsmentioning
confidence: 99%
“…Lead‐based perovskites have benefitted immensely from compositionally tuning away from methylammonium lead iodide (MAPbI 3 ), giving rise to record‐breaking power conversion efficiencies (PCEs), impressive device stabilities, and broadly tunable optoelectronic properties suitable for a vast range of useful applications. [ 1–8 ] However, there is currently significant motivation to pursue lead‐free perovskite derivatives for a number of reasons that extend beyond the manufacturing and environmental concerns associated with Pb. [ 9–11 ] Group 15 metals, such as arsenic, bismuth, and antimony, have shown promise as alternates to Pb outside of Group 14.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the Cl element can be successfully incorporated into the low-dimensional perovskite crystal lattice to improve the sample morphology and carrier transport mobility; while the process cannot be achieved in the conventional 3D perovskites. [118] Figure 12. Schematics of a) lateral and b) vertical devices for in-plane and out-of-plane carrier transport, respectively.…”
Section: Easy Processmentioning
confidence: 99%
“…In this case, Sn‐based 2D perovskites have been identified as suitable alternatives, while they are still hindered by the instability in the air environment. [ 50 ] Loh et al [ 51 ] reported a Sn‐based hybrid organic–inorganic 2D perovskite of (FSA) 2 SnI 4 with enhanced air stability, using 2‐(4‐(3‐fluoro)stilbenyl)ethanammonium (FSA + ) as the organic cations. The water instability of (FSA) 2 SnI 4 perovskite is ascribed to the water resistance of fluorinated organic chains, as a concrete effect of strongly cohesive bonding contained the H bonding, CH‐X type of H bonding, weak interlayer of F‐F interactions, and weak aspectant type of π‐π interaction.…”
Section: Synthesis Structure and Physical Properties Of 2d Metal‐hamentioning
confidence: 99%